دراسة بعض العوامل المؤثرة على السمات الشخصية للتلاميذ الصم (دراسة حالة بمركز الجبل لتأهيل الصم وضعاف السمع بدار الرعاية بمدينة البيضاء) - الهيتى , على السيد إبراهيم (Scientific Journal of University of Benghazi, 2022)
Humanity has known deafness since the beginning of time, considering it a social and psychological problem to be dealt with. The study of the personalities of people afflicted with deafness is one of the significant topics in this field. This research examined the factors influencing the personality characteristics of deaf pupils, as hearing impaired students have adaptive problems in their social, professional, mental, linguistic and academic development that affect their personality. The trait of introversion and distrust of others has been found to be a dominant feature of the personality of deaf pupils, while the characteristic of suspicion of others is at the lower end of the list. This can be due to the instinctive strength of these deaf pupils and the nature of their lives, most of which are in the home, with heightened attention from their parents and families. The study found differences between males and females in personality traits, where these were in favor of the female students. The study also found that discrepancies in the personality characteristics of deaf students were attributable to the variable age, family income and educational levels of the father and mother. The research recommends affording more attention to deaf pupils, with the provision of psychological, social, vocational and educational services as well as emphasizing the importance of the role of the family in alleviating the difficulties faced by deaf students as well as working to educate families on how to deal with deaf members.